PELATIHAN PEMBUATAN MODUL DIGITAL BERBASIS FLIPBUILDER PADA TENAGA PENDIDIKAN DI SMAN 6 BATANGHARI - Anny Wahyuni; Muhammad Adi Saputra; Andre Mustofa meihan; Destri Yaldi; Lisa Rukmana (Penerbit Widina, Widina Media Utama, 2024)
raining in making digital modules as learning aids has become a necessity for educators to improve the effectiveness and efficiency of the learning process in the classroom. the purpose of this service is to improve the quality of learning through the use of technology in the preparation of innovative and interactive teaching materials in the form of e-modules. the method used is the first, determining the location of the activity. Second, determining target partners, third, types of activities. Fourth, the activity stage is divided into the preparation stage, the implementation stage and the reflection stage. the results obtained in this training are teachers at SMAN 6 Batanghari who participated in this training totaling 26 people. This teacher knows, recognizes and understands the Flipbuilder application and is proficient in making e-modules using this application so that they can be used as teaching materials for students. The conclusion of this service is that this training is very useful for teachers and students in the form of e-module products.ABSTRAKPelatihan pembuatan modul digital sebagai alat bantu pembelajaran telah menjadi kebutuhan bagi tenaga pendidik untuk meningkatkan efektivitas dan efisiensi proses pembelajaran di kelas. tujuan pengabdian ini untuk meningkatkan kualitas pembelajaran melalui pemanfaatan teknologi dalam penyusunan materi ajar yang inovatif dan interaktif dalam bentuk e-modul. metode yang digunakan adalah yang pertama, penentuan lokasi kegiatan. Kedua, menentukan mitra sasaran, ketiga, Jenis Kegiatan. Keempat, tahap kegiatan yang dibagi kedalam tahap persiapan, tahap pelaksanaan dan tahap refleksi. hasil yang didapat dalam pelatihan ini adalah guru-guru di SMAN 6 Batanghari yang ikut dalam pelatihan ini berjumlah 26 orang. Guru ini mengetahui, mengenal dan memahami aplikasi Flipbuilder serta mahir dalam pembuatan e-modul menggunakan aplikasi ini sehingga bisa di jadikan bahan ajar untuk siswa. Kesimpulan dari pengabdian ini bahwa pelatihan ini sangat bermanfaat bagi guru dan siswa dalam bentuk produknya e-modul.